ВИЗУАЛИЗАЦИЯ ДАННЫХ И КРОСС-АНАЛИЗ АСТРОНОМИЧЕСКИХ КАТАЛОГОВ - Китаева, М. А.; Самодуров, В. А.; Думский, Д. В.; Исаев, Е. А. (Одеські астрономічні публікації, 2011)
On PRAO’s web-site we have for several years been developing a database of the major and most important astronomical catalogs most frequently used by radio astronomers. These are survey catalogs of radio sources observed on various radio frequencies (and also frequencies of other spectrums), catalogs of major heavenly objects studied in radio astronomy, etc. The astronomical catalogs data is operating in on-line mode on the site called “Radio-astronomer’s working environment”, http://astro.prao.ru/db/. It already contains some tens of the major astronomical catalogs. Starting in 2011 the database has been actively equipped with means of graphical visualisation of the data and cross-analysis of the catalogs among themselves. These means will serve as the base for statistical processing and cross-analysis of various astronomical catalogs. For example, catalogs of radio-sources on various frequencies can be widely used in further theoretical and experimental research of properties of both extragalactic radiation sources and objects in our own Galaxy. Statistical cross-analysis of the data from various catalogs can be used both for research of properties of separate objects and for the statistical analysis of properties of various classes of objects. It can also be used for research of properties of the catalog data like completeness, reliability, calibration of catalogs etc. For the tasks at hand we are developing tools for graphic representation of the data from several catalogs within a chosen sector on the sky; representation of the data and the statistical analysis of the main parameters of each catalog; and statistics of cross-identifications of the catalogs selected by the user.